Thermal Expansion and Mode Grüneisen Parameters in Lithium - Prasad B. (My University, 2025)
The mode Grüneisen parameters γqj, the mean value of Grüneisen parameter γM, and the thermal expansion coefficient γM are computed for b.c.c. lithium employing the model potential proposed by Krasko and Gurskü. The present results are compared with available experimental data. Reasonable agreement between theory and experiment is obtained. Copyright © 1984 WILEY‐VCH Verlag GmbH & Co. KGaA